circRNAs as Epigenetic Regulators of Integrity in Blood–Brain Barrier Architecture: Mechanisms and Therapeutic Strategies in Multiple Sclerosis - D'Aversa, Elisabetta; Salvatori, Francesca; Vaccarezza, Mauro; Antonica, Bianca; Grisafi, Miriana; Singh, Ajay Vikram; Secchiero, Paola; Zauli, Giorgio; Tisato, Veronica; Gemmati, Donato (MDPI AG, 2024)
Multiple sclerosis (MS) is a chronic inflammatory neurodegenerative disease leading to progressive demyelination and neuronal loss, with extensive neurological symptoms. As one of the most widespread neurodegenerative disorders, with an age onset of about 30 years, it turns out to be a socio-health and economic issue, thus necessitating therapeutic interventions currently unavailable. Loss of integrity in the blood–brain barrier (BBB) is one of the distinct MS hallmarks. Brain homeostasis is ensured by an endothelial cell-based monolayer at the interface between the central nervous system (CNS) and systemic bloodstream, acting as a selective barrier. MS results in enhanced barrier permeability, mainly due to the breakdown of tight (TJs) and adherens junctions (AJs) between endothelial cells. Specifically, proinflammatory mediator release causes failure in cytoplasmic exposure of junctions, resulting in compromised BBB integrity that enables blood cells to cross the barrier, establishing iron deposition and neuronal impairment. Cells with a compromised cytoskeletal protein network, fiber reorganization, and discontinuous junction structure can occur, resulting in BBB dysfunction. Recent investigations on spatial transcriptomics have proven circularRNAs (circRNAs) to be powerful multi-functional molecules able to epigenetically regulate transcription and structurally support proteins. In the present review, we provide an overview of the recent role ascribed to circRNAs in maintaining BBB integrity/permeability via cytoskeletal stability. Increased knowledge of the mechanisms responsible for impairment and circRNA’s role in driving BBB damage and dysfunction might be helpful for the recognition of novel therapeutic targets to overcome BBB damage and unrestrained neurodegeneration.